КОНЦЕПТУАЛЬНЫЕ ПОДХОДЫ К ПРОБЛЕМЕ ЛИЧНОСТНЫХ РЕСУРСОВ - Carolina PLATON; Natalia Buraga (Moldova State University, 2016)
В статье рассматриваются основные методологические и концептуальные проблемы, связанные с понятием личностных ресурсов. Обобщаются имеющиеся подходы к выявлению ресурсов личности. Ресурсы личности анализируются как резерв личности и личностный потенциал. ABORDĂRI CONCEPTUALE ALE PROBLEMEI RESURSELOR PERSONALE În articol sunt examinate principalele probleme metodologice şi conceptuale legate de noţiunea "resurse personale". Este prezentată o generalizare a abordărilor privind resursele personalităţii, fiind considerate drept rezervă a personalităţii şi potenţial personal.  CONCEPTUAL APPROACHES TO THE PROBLEM OF PERSONAL RESOURCES This article examines the main methodological and conceptual problems associated with the notion of personal resources. There are generalized the existing approaches to the personal resources. Approaches to resources like the individual reserve and personal potential are also analyzed.